2021
DOI: 10.1039/d1ra03091d
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of trisindolines: natural occurrence, synthesis and bioactivity

Abstract: This in-depth review of trisindolines covers their natural occurrence in addition to several routes of synthesis and catalysts used. The biological activities of trisindolines have been discussed with a special emphasis on the structure–activity relationship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 112 publications
(137 reference statements)
0
17
0
Order By: Relevance
“…This proves that isatin is one of the key intermediates formed under condition‐B. On the other hand, literature study reveals that the acid catalyzed condensation of isatin and indole gives trisindoline [28] which is not formed in our reactions. However, acid catalyzed reaction of isatin and oxindole provides isoindigo [23] .…”
Section: Resultsmentioning
confidence: 54%
“…This proves that isatin is one of the key intermediates formed under condition‐B. On the other hand, literature study reveals that the acid catalyzed condensation of isatin and indole gives trisindoline [28] which is not formed in our reactions. However, acid catalyzed reaction of isatin and oxindole provides isoindigo [23] .…”
Section: Resultsmentioning
confidence: 54%
“…As a result of this surge, numerous methods have been devised for the production of naturally occurring BIMs and their functionalized analogues (see Scheme 1 ). 7 , 11 , 33 , 34 Interestingly, most methods utilize 3-indole aromatic alcohols to afford symmetrical and unsymmetrical 3,3′-BIMs using a condensation strategy with appropriate nucleophiles. 19 , 35 In addition, the most common reaction protocols used in the synthesis include expensive and excess amounts of catalysts such as Cu-catalysts, 36 TsOH, Ga(OTf) 3 , Zn(OTf) 2 , etc.…”
Section: Introductionmentioning
confidence: 99%
“…3,3′-Bisindolylmethane (BIM) and its functionalized class of natural products were originally isolated from cruciferous plants and terrestrial and marine organisms and shown to contain a broad array of medicinal properties. Key members of this class of natural products include arundine, vibrindole A, streptindole, arsindoline A, tris­(1 H -indol-3-yl)­methane, and trisindoline (Figure ). A unique structure of this bioactive intermediate contains two indole units which are responsible for exhibiting a range of essential biological activities such as anti-neurodegenerative, anti-inflammatory, anticancer, antibiotic, insecticidal, antimicrobial, antifungal, and antioxidant properties (Figure ). , Interestingly, some of these BIM derivatives are used as a sedatives in the treatment of AIDS, chronic fatigue, irritable bowel syndrome, and cancer, while bis­(indolyl)­arylmethane-bearing compounds are used as drugs for Parkinson’s disease, obesity, and bacterial and oncolytic viruses. , In addition, BIMs have also been found to have the potential to normalize abnormal cell growth associated with cervical dysplasia …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In both naturally occurring and synthetic compounds, indole derivatives are recognized as a privileged structural motif . Statistically, C3-functionalized indole-based compounds are most abundant among all the indole derivatives with various biological activities (Figure a) . 3-Positioned functionalization of the indole ring is a pivotal synthetic route to prepare a number of promising therapeutic agents .…”
mentioning
confidence: 99%